3(c*c)+7(c*c)=

Simple and best practice solution for 3(c*c)+7(c*c)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(c*c)+7(c*c)= equation:


Simplifying
3(c * c) + 7(c * c) = 0

Multiply c * c
3(c2) + 7(c * c) = 0

Multiply c * c
3c2 + 7(c2) = 0

Combine like terms: 3c2 + 7c2 = 10c2
10c2 = 0

Solving
10c2 = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Divide each side by '10'.
c2 = 0.0

Simplifying
c2 = 0.0

Take the square root of each side:
c = {0.0}

See similar equations:

| 9y-8-5y=5y-7 | | (x+2)/(x^3+8) | | 4y=3*5-2+7 | | 6y-14=4y-2 | | n/4=12 | | 6s-10=w | | y=1/2(-6)-3 | | 3m-2n-7m-n= | | -3-y=-11 | | 5/25 | | 2(a-1)=2(1.4a+3) | | 7n-10n= | | 5m+7m+m= | | -12+20x=1-10x | | 6/x=9/15 | | 60/12=x/8 | | 0=16r^2-81s^2 | | 5/20=x/4 | | 0=9x^2+6x-8 | | 2/5=4/x | | -25x+17=12x-8 | | 3x^2+7x-26=0 | | 14y^2-12y=0 | | 4m+n=p | | 1/3=x/9 | | 1/3(h+6)=5/6h | | 6e+6=4e+8 | | 8-711/16 | | 5b-15=7b-14 | | 2x+4(2x+15)=130 | | y=-1/2(-6)+2 | | -4bcz-95xyz=99999b |

Equations solver categories